Gambaran Persepsi Peserta Didik tentang Kebermanfaatan Buku Pengayaan Ujian Nasional Biologi - Fajar Adinugraha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
The objective of research is to describe the form and content of the book of enrichment for biology national exam. The title of this book is PREDIKSI. This research also describes the perceptions of students on the advantage of the book PREDIKSI. This research is a descriptive research. The methods applied for the research were study literature and survey. There were 21 samples taken from students who were using the book PREDIKSI with the number of respondents 21 students. The enrichment book entitled PREDIKSI is a book consisting of material summaries used for the enrichment sessions of the biology national exam. This book are contains of a summary of the biology materials, practical memorizing tips, short answeres, essay exercises, and a discussion of questions. The students' perceptions about this book are very positive. It is shown from the average score of students' perceptions of the usefulness of the book is 4.19. This book is expected to be the solution for the students in overcoming anxiety toward Biology National Exam. Keywords: content of PREDIKSI book, students’ perception, advantage